2017
DOI: 10.1159/000449087
|View full text |Cite
|
Sign up to set email alerts
|

Does the Introduction of Biosimilars Change Our Understanding about Treatment Modalities for Inflammatory Bowel Disease?

Abstract: Background: Biological agents, mainly tumor necrosis factor-α inhibitors, play an important role in the treatment of inflammatory bowel disease (IBD). These drugs are expensive and constitute a major cost in the IBD care. In 2013, the first biosimilar monoclonal antibody, infliximab (IFX), was approved in the EU. Key Messages: There has been considerable skepticism regarding the use of biosimilars. Both clinicians and patients have questioned the safety and efficacy of these new drugs. In particular, the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In clinical practice, extrapolation of molecules in the same class sharing the same mechanism of action from adult to pediatric (6,7) or across indications (8,9) is common in case there are not enough data available or when clinical trials are ongoing. Extrapolation allows keeping the cost of BioS competitive with subsequent greater market availability (4,10,11). On the other hand, proven mechanism of action (eg, TNF blocking) in different diseases may not result in same clinical efficacy (9,12,13).…”
Section: Extrapolationmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical practice, extrapolation of molecules in the same class sharing the same mechanism of action from adult to pediatric (6,7) or across indications (8,9) is common in case there are not enough data available or when clinical trials are ongoing. Extrapolation allows keeping the cost of BioS competitive with subsequent greater market availability (4,10,11). On the other hand, proven mechanism of action (eg, TNF blocking) in different diseases may not result in same clinical efficacy (9,12,13).…”
Section: Extrapolationmentioning
confidence: 99%
“…As IBD is a complex disease with differences between pediatric-onset and adult-onset disease, the decisions of regulatory agencies on extrapolation of indications to IBD were challenged by both adult (ECCO) and pediatric (ESPGHAN) gastroenterology societies (14,15). In 2014, Health Canada did not approve IFX BioS for IBD due to lack of clinical data, molecular glycosylation differences and uncertainty resulting from small differences in antibody-dependent cell-mediated cytotoxicity (9,10,(16)(17)(18). However, in view of the emerging data, Health Canada has now recommended BioS IFX for all the indications of originator IFX by extrapolation (19).…”
Section: Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation
“…The patent for the IFX originator administration of these agents vary substantially between countries. For example, Health Canada (2014) did not approve IFX BS for IBD due to insufficient amount of clinical data, molecular glycosylation differences and uncertainty resulting from small differences in antibody-dependent cell-mediated cytotoxicity [92][93][94][95][96]. Nevertheless, in view of the emerging data, Health Canada has now recommended BS IFX for all the indications of originator IFX by extrapolation [97].…”
Section: Biosimilars and Cost-effectivenessmentioning
confidence: 99%
“…Nevertheless, in view of the emerging data, Health Canada has now recommended BS IFX for all the indications of originator IFX by extrapolation [97]. In other countries, BS approval by regulatory agencies, a number of clinical data reports were published on BS in both adult and pediatric IBD [93,[98][99][100][101][102][103][104][105][106]. The NOR-SWITCH RCT trial [107] found comparable safety and efficacy in patients including IBD switching from IFX to CT-P13.…”
Section: Biosimilars and Cost-effectivenessmentioning
confidence: 99%